Status prawny posła na Sejmie PRL (w świetle nowych regulacji prawnych) - Rost, Antoni; Suchocka, Hanna (Wydział Prawa i Administracji UAM, 1986)
The subject matter of the present article is concerned with a presentation of the legal status of a member of the Diet of the Polish People's Republic in the light of the new legal regulation: electoral regulations to the Diet, and the first Polish statute relative to the rights and obligations of a member of the PPR Diet. The new regulation maintains the present construction of a mandate to represent, generating additional institutional guarantees for the electors to have the deputies duties realized. The act of the duties and rights of members of the Diet enumerates the material forms of the execution of the duties, as for istance open and circle deputy meetings, inspections of employing institutions, permanent duty hours, press publication of deputy statements, etc. Parallel to the said obligations, the rights of members of the Diet have been extended, particularly in respect to guaranteed rights of a deputy to the activity towards institutions and organs external to the Diet. Such deputy rights as the right to information and the right to intervention have been extended and strengthened. The previous catalog of rights of a deputy in the Diet, is maintained, i.e. the right to take the floor, the right to vote, he right of legislative initiative, the right to interpellate, lodge questions, the right to being organized in deputy clubs according to their party membership. The formal, personal immunity has been maintained, the material immunity of responsibility is not adopted. The act of the duties and rights of members of the Diet regulated also, to a larger extent the protection of employment relation of a deputy, both during his term and in two years after its completion, the latter being a novelty. The previous social benefits, especially the right to salaries and free passages.
Legal Status of a Member of the Diet of the Polish People's Republic (in the Light of New Legal Regulation)